Проблемы вещно-правовой защиты права собственности - Timofeyeva, Mariya (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The aim of the study is to evaluate the property rights protection system in the civil law system of the Russian Federation. The author present the law instruments that owner and possessor are entitled to by focusing on the law regulation and judicature.